Analysis of Morphometric Properties and Their Hydrological Significance in the Rokhana Wadi Basin: Using Geographic Information Systems (GIS) (Raparin Journal of Humanities (RJH), 2025)
This research investigates the relationship between geomorphological variables and their hydrological implications. It uses data provided by Geographic Information Systems (GIS) to interpret digital elevation models (DEMs) in the Rukhaneh Valley Basin in northeastern Iraq. It covers an area between the mountainous and semi-mountainous areas of the Kurdistan Region. It belongs to the Sara Mountain Range, which is a watershed between the Rukhaneh and Tanjoro basins in the upper regions of it, that is, the source area. In the northeast, there is the Diwaneh Basin, in the east, and the AwaSpi Basin in the west. It borders the Khasah Basin, and it covers a vast area of 3,468.88 km 2. It empties into Lake Azim, the seventh-largest lake. The Rukhaneh Basin has a maximum length of 118.52 km. It is split into two levels, namely high and low, as well as three levels of climatic regions. It is located astronomically between 30 48 -34 20 04, and 2018 0025 -45. The research aims to examine the morphometric features of the Wadi Rukhana Basin and their connection with the hydrological variables and implications, the consequent rise in water discharges and floods and their destructive impact and ways of managing the risks to alleviate the adverse effect of the same on human activity. The study reached a set of results, the most significant of which, based on morphometric characteristics and hydrological parameters, is that there is no risk of flash floods.